Myokines in Home-Based Functional Electrical Stimulation-Induced Recovery of Skeletal Muscle in Elderly and Permanent Denervation - Sascha Sajer; Giulio Sauro Guardiero; Bianca Maria Scicchitano (PAGEPress Publications, 2018)
Neuromuscular disorders, disuse, inadequate nutrition, metabolic diseases, cancer and aging produce muscle atrophy and this implies that there are different types of molecular triggers and signaling pathways for muscle wasting. Exercise and muscle contractions may counteract muscle atrophy by releasing a group of peptides, termed myokines, to protect the functionality and to enhance the exercise capacity of skeletal muscle. In this review, we are looking at the role of myokines in the recovery of permanent denervated and elderly skeletal muscle tissue. Since sub-clinical denervation events contribute to both atrophy and the decreased contractile speed of aged muscle, we saw a parallel to spinal cord injury and decided to look at both groups together. The muscle from lifelong active seniors has more muscle bulk and more slow fiber-type groupings than those of sedentary seniors, demonstrating that physical activity maintains slow motoneurons that reinnervate the transiently denervated muscle fibers. Furthermore, we summarized the evidence that muscle degeneration occur with irreversible Conus and Cauda Equina syndrome, a spinal cord injury in which the human leg muscles may be permanently disconnected from the peripheral nervous system. In these patients, suffering with an estreme case of muscle disuse, a complete loss of muscle fibers occurs within five to ten years after injury. Their recovered tetanic contractility, induced by home-based Functional Electrical Stimulation, can restore the muscle size and function in compliant Spinal Cord Injury patients, allowing them to perform electrical stimulation-supported stand-up training. Myokines are produced and released by muscle fibers under contraction and exert both local and systemic effects. Changes in patterns of myokine secretion, particularly of IGF-1 isoforms, occur in long-term Spinal Cord Injury persons and also in very aged people. Their modulation in Spinal Cord Injury and late aging are also key factors of home-based Functional Electrical Stimulation - mediated muscle recovery. Thus, Functional Electrical Stimulation should be prescribed in critical care units and nursing facilities, if persons are unable or reluctant to exercise. This will result in less frequent hospitalizations and a reduced burden on patients' families and public health services.